THE EFFECT OF HEADMASTERS' LEADERSHIP STYLE, SUPERVISION ABILITY AND WORK CLIMATE ON THE PERFORMANCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN PRABUMULIH CITY - Lutfi Lutfi; Nyayu Khodijah; Akmal Hawi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research was motivated by the fact that there were several principals at SMPN Prabumulih, sometimes in certain aspects of leadership they still rely too much on their subordinates, including waiting for ideas from their subordinates. Then, teacher performance is required to plan, implement and assess learning programs and train students during the learning process. This study aims to analyze the influence of the Principal's Leadership Style, Supervision Ability, and Work Climate, on the Performance of Islamic Religious Education (PAI) Teachers in Junior High Schools in Prabumulih City. The method used in this study was a quantitative method. This research is a causal-comparative research. Data was collected by distributing questionnaires. Data wasanalyzed by using data normality test, autocorrelation test, linearity test, multicollinearity test and path analysis. From the results of data analysis, the following findings were obtained; 1) There is a positive influence between the principal's leadership style and academic supervision ability; 2) There is a positive influence between the principal's leadership style on the work climate; 3) There is a positive influence between the ability of academic supervision on the work climate; 4) There is a positive influence between the principal's leadership style on teacher performance; 5) There is a positive influence between academic supervision ability on teacher performance and 6) There is a positive influence between work climate on teacher performance.